Revision of the genus Stenoscelis Wollaston (Coleoptera: Curculionidae: Cossoninae) of Japan - Inoue, Shûgo (Zootaxa, 2025)
The Japanese species of the genus Stenoscelis Wollaston, 1861 are revised. Nine species, S. acutipennis Zherikhin, 1991, S. brevithoracicus Inoue sp. nov., S. cavirostris Inoue sp. nov., S. longisetosus Konishi, 1956, S. aceri Konishi, 1962, S. matobai Inoue sp. nov., S. reniformis Inoue sp. nov., S. gracilitarsis Wollaston, 1873, and S. ogasawarensis Inoue sp. nov., are recognized. Stenoscelis cryptomeriae Konishi, 1962 syn. nov. is a new junior synonym of S. longisetosus Konishi, 1956. All species are described or redescribed, and a key to the Japanese species is presented.